Hyperthermia and cisplatin combination therapy promotes caspase-8 accumulation and activation to enhance apoptosis and pyroptosis in cancer cells - Guanghui Zi; Jin Chen; Yatu Peng; Yue Wang; Baowei Peng (International Journal of Hyperthermia)
Background Hyperthermia can play a synergistic role with chemotherapy in combination therapy. Although the association between caspase activation, apoptosis, and pyroptosis have been published for both cisplatin (CDDP) and hyperthermia therapies independently, the interactions between these molecular pathways in combination therapy are unknown. The present study aimed to investigate the possible interactions between caspase 8 activation, apoptosis, and pyroptosis in combination therapy.Methods Cells were treated with CDDP (15 µg/ml), followed by hyperthermia at optimized temperature (42.5 °C) in water-bath. After combination therapy, cell viability was analyzed by CCK-8, and cell death was analyzed by Annexin-V-FITC/PI and caspases activation. Immuno-staining and co-immuno-precipitation were used to examine the interaction between p62 and caspase-8. Pyroptosis was investigated by western blotting and transmission electron microscopy. E3 ligase Cullin 3 was knockdown by siRNA. In addition, caspase-8 activation was modulated by CRISPR-Cas9 gene-editing or pharmacological inhibition.Results Combination therapy promoted K63-linked polyubiquitination of caspase-8 and cellular accumulation of caspase-8. In turn, polyubiquitinated caspase-8 interacted with p62 and led to the activation of caspase-3. Knockdown of the E3 ligase Cullin 3 by siRNA reduced caspase-8 polyubiquitination and activation. In addition, combination therapy induced release of the pore-forming N-terminus from gasdermins and promoted pyroptosis along with caspase-8 accumulation and activation. Knockdown of caspase-8 by CRISPR/Cas9 based gene editing reduced the sensitivity of tumor cells to apoptosis and pyroptosis.Conclusions Our study presented a novel mechanism in which hyperthermia synergized with chemotherapy in promoting apoptosis and pyroptosis in a caspase-8 dependent manner.